Mitochondrial DNA Base Editing: Good Editing Things Still Come in Small Packages - Bacman, Sandra R; Moraes, Carlos T (Molecular cell, 2020)
The collaborative work of two HHMI groups, one at the University of Washington and the other at the Broad Institute of MIT and Harvard, led to the development of a novel molecular tool to edit single bases in the mtDNA (Mok et al., 2020).The collaborative work of two HHMI groups, one at the University of Washington and the other at the Broad Institute of MIT and Harvard, led to the development of a novel molecular tool to edit single bases in the mtDNA (Mok et al., 2020).